Identification of the Minimal Replicon of Lactococcus lactis subsp. lactis UC317 Plasmid pCI305 - Hayes, Finbarr (1990)
Replication functions of the stable, cryptic 8.7-kilobase (kb) plasmid pCI305 from multi-plasmid-containing Lactococcus lactis subsp. lactis UC317 were studied. Analysis of this replicon was facilitated by the construction of replication probe vectors that consisted of the pBR322 replication region, a pUC18-derived multiple cloning site, and either the cat gene of pC194 (pCI341; 3.1 kb) or the erm gene of pAMβ1 (pCI3330; 4.0 kb). Plasmid pCI305 was introduced into plasmid-free L. lactis subsp. lactis MG1363Sm, a streptomycin-resistant derivative of MG1363, by a transformation procedure with the 75-kb lactose-proteinase plasmid pCI301 of UC317 as a marker plasmid. A combination of transposon Tn5 mutagenesis and subcloning in pCI341 and pCI3330 with individual Tn5 insertions around the replication region facilitated the identification of a 1.6-kb minimal replicon on pCI305. This region was separable into two domains: (i) a 1.3-kb region (repB) encoding a trans-acting function (in vitro transcription-translation studies suggested the involvement of a 48-kilodalton protein); and (ii) a 0.3-kb region (repA) sufficient to direct replication when provided with repB in trans and thus probably containing the origin of replication. Lactococcus-Escherichia coli shuttle vectors based on the pCI305 replication region were constructed.